The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2018
DOI: 10.1002/maco.201810156
|View full text |Cite
|
Sign up to set email alerts
|

Steam oxidation resistance of plasma sprayed chromium‐containing coatings at 1200 °C

Abstract: In order to improve the high‐temperature steam oxidation resistance of Zircaloy fuel claddings, chromium‐containing coatings (Cr3C2‐NiCr and NiCr) were deposited on a Zr‐4 substrate by air plasma spray. The steam oxidation resistance of the two coatings was evaluated at 1200 °C under atmospheric pressure. The weight changes, phase compositions, and microstructures of the coatings before and after the oxidation test of 1 h were characterized. Results revealed that the Cr3C2‐NiCr coating effectively protected Zr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 27 publications
0
4
0
Order By: Relevance
“…However, the coated samples showed poor corrosion resistance in supercritical water at 400 • C and 10.3 MPa, caused by a bimetallic effect (this coating can build up bimetallic couple with the Zr-2.5Nb alloy, resulting in the acceleration of the corrosion rate). Yang et al demonstrated high oxidation resistance of 120 µm-thick HVOF Cr 3 C 2 -NiCr coating at 1200 • C in steam for 1 h due to the formation of a dense chromia scale [149]. However, the high coating thickness and heterogeneous/porous microstructure formed by the HVOF method may limit the usefulness of such coatings for ATF Zr claddings.…”
Section: Carbide Coatingsmentioning
confidence: 99%
“…However, the coated samples showed poor corrosion resistance in supercritical water at 400 • C and 10.3 MPa, caused by a bimetallic effect (this coating can build up bimetallic couple with the Zr-2.5Nb alloy, resulting in the acceleration of the corrosion rate). Yang et al demonstrated high oxidation resistance of 120 µm-thick HVOF Cr 3 C 2 -NiCr coating at 1200 • C in steam for 1 h due to the formation of a dense chromia scale [149]. However, the high coating thickness and heterogeneous/porous microstructure formed by the HVOF method may limit the usefulness of such coatings for ATF Zr claddings.…”
Section: Carbide Coatingsmentioning
confidence: 99%
“…Up to now, many types of coating materials have been developed, including MAX phase coatings [10][11][12][13][14], carbide coatings [15,16], nitride coatings [17][18][19][20], pure metal coatings [21][22][23][24][25][26] and alloy coatings [27][28][29][30][31][32]. Previous studies show that MAX phase coatings such as Ti-Al-C and Cr-Al-C are susceptible to cracking through the coating during heat treatment, water corrosion, and high temperature steam oxidation [33,34].…”
Section: Introductionmentioning
confidence: 99%
“…However, the HT oxidation experiments performed so far have focused mainly on the performance of the ideal coating without defects [11][12][13][14]. According to existing studies, the HT steam oxidation process of Cr-coated Zr-based alloys can be divided into three groups.…”
Section: Introductionmentioning
confidence: 99%